2016
DOI: 10.1017/cbo9781316584989
|View full text |Cite
|
Sign up to set email alerts
|

Epigram, Art, and Devotion in Later Byzantium

Abstract: This book explores the nexus of art, personal piety, and self-representation in the last centuries of Byzantium. Spanning the period from around 1100 to around 1450, it focuses upon the evidence of verse inscriptions, or epigrams, on works of art. Epigrammatic poetry, Professor Drpić argues, constitutes a critical - if largely neglected - source for reconstructing aesthetic and socio-cultural discourses that informed the making, use, and perception of art in the Byzantine world. Bringing together art-historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In Byzantine artistic theory and practice, κόσμος was used with the meaning of order and ornament which, as I. Drpicá rgued, 'enhanced the representation of images, organized their appearance, and communicated sanctity'. 73 Drpićalso convincingly suggested that in late Byzantium, κόσμος, as the adornment of sacred objects, was used abundantly because it responded to aesthetic norms as well as to the pervasive understanding that κόσμος could partake of the object's sanctity. 74 While Bryennios uses κόσμος with the parallel meaning of the created world, he also integrates the notion of an orderly ornamentation.…”
Section: Didactic Techniques In the Forty-nine Chapters: Rhetorical Amentioning
confidence: 99%
“…In Byzantine artistic theory and practice, κόσμος was used with the meaning of order and ornament which, as I. Drpicá rgued, 'enhanced the representation of images, organized their appearance, and communicated sanctity'. 73 Drpićalso convincingly suggested that in late Byzantium, κόσμος, as the adornment of sacred objects, was used abundantly because it responded to aesthetic norms as well as to the pervasive understanding that κόσμος could partake of the object's sanctity. 74 While Bryennios uses κόσμος with the parallel meaning of the created world, he also integrates the notion of an orderly ornamentation.…”
Section: Didactic Techniques In the Forty-nine Chapters: Rhetorical Amentioning
confidence: 99%
“…A few of the earliest icons on panels do carry calligraphic complete frames. 35 One well-known image is the seventh/eighth century Maiestas Domini icon in the Santa Katrina monastery. 36 Only one manuscript from the mid-tenth century, known as the Leo Sacellarios Bible or Queen Cristina Bible (Biblioteca Apostolica Vaticana, MS Reg.…”
Section: Developmental Influences From Surrounding Culturesmentioning
confidence: 99%
“…However, as this system creates a flipped line requiring one to turn the manuscript in order to read the frame's of 895 CE," 184-86; Leila Avrin, "Note on Micrography: A Jewish Art Form," Journal of Jewish Art 6 (1979): 114; Gutmann, Hebrew Manuscript Painting, 18; Gutmann, "The Messianic Temple," 172; J. N. Hillgarth and B. Narkiss, "A List of Hebrew Books (1330) and a Contract to Illuminated Manuscripts (11350) from Majorca," Revue des etudes Juives 3 (1961): 319; Narkiss,Hebrew Illuminated Manuscripts,29,69;and Milstein,"Hebrew Book Illumination in the Fatamid Era,Islam and Muslim Art,227. 58 Schlosberg,"RaSaG's Attitude Towards the Islam,[33][34][35] Dan Pagis, Poetry Aptly Explained (Jerusalem: Magnes Press, 1993), 90.…”
Section: Mise En Cadre and Its Relation To Forming Textmentioning
confidence: 99%
“…The vogue for this poetic form may have also been one of the consequences of the fact that epigrammatic poetry flourished in the Palaiologan era. 47 Judging by what research into this subject has come up with, the content of the epigram on our staurotheke is in full conformity with the character and purpose of the object itself. Namely, recent research-especially Wolfram Hörandner's specialist studies-has shown that the repertoire of motifs in Byzantine epigrams relating to the True Cross includes a few typical ones, the motif of the cross as protector holding the central place.…”
mentioning
confidence: 99%
“…Some of these models were especially popular, such as the story of the widow's mite, Gregory of Nazianzus' favourite. 38 The parable of the widow's mite was widely used in Serbia too. 39 It is indicative that it appears at the very beginning of the fourteenth century, in King Milutin's charter for the monastery of Hilandar's pyrgos of St.…”
mentioning
confidence: 99%